Some features on Tra Lu village (Nam Dinh) in the early nineteenth century as seen from Tra Lu land register - Hien, Dinh Thi Thuy (VNU Journal of Science: Social Sciences and Humanities; Vol 23 No 5E, 2007)
Abstract: